Policy and Regulatory Frameworks Guiding Nigerian Professionals - ETINAGBEDIA, Goodluck (Management Research and Behavior Journal, 2024)
This study which is qualitative in nature investigates policy and regulatory frameworks guiding Nigerian professionals. This employed historical method and data collected was analyzed using content analysis method. The study concluded that the Nigerian's efforts to achieve transparent and accountable public service are gravely hampered by the issue of underqualified, incompetent, and poorly trained employees. An additional perspective on this is the improper staffing decisions that lead to the appointment or hiring of individuals for roles for which they are either politically appointed or lack the necessary training or experience. These elements undermine the goal of professionalism in public administration, which is instead based on applying skills learned through education and training to achieve excellence in performance under the guidance of established codes of conduct.